SISTEM INFORMASI BUKU TAMU BERBASIS WEB - Prastika Buya Hakim; Basmalia Basmalia; Nur Azise (Jurnal Riset Sistem Informasi, 2025)
Manual guestbook systems frequently encounter challenges like inefficiency, data loss, and trouble interpreting recorded information. The goal of this research is to create a web-based guestbook information system in order to address these issues. This approach is intended to make capturing visitor data easier, lower the chance of mistakes, and enable users to receive notifications automatically. The requirements analysis, system design, implementation, and testing phases are all part of the waterfall paradigm of system development. This information system is intended to increase the effectiveness of guest books in associated institutions.